Kontribusi Koordinasi Mata-Tangan, Kelentukan Pergelangan Tangan, dan Daya Ledak Otot Lengan Terhadap Kemampuan Passing atas Permainan Bola Voli Peserta Ekstrakurikuler - Suparman Suparman; Ariana Asri; Haeril Haeril (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2021)
This study aims to determine the contribution of hand-eye coordination, hand muscle flexibility, and arm explosive power to the passing ability of the male extracurricular members of SMPIT Al-fityan Gowa. This research belongs to the type of descriptive research with quantitative methods. The population is all male extracurricular participants of SMPIT Al-Fityan Gowa with a sample of 30 people taken by random sampling. The data analysis technique used is descriptive analysis, normality test, linearity test, simple regression test and multiple regression test using computer facilities through the SPSS program. Based on the analysis of the data obtained the results: 1). There is a significant contribution of eye-hand coordination to the ability to pass over the coefficient of determination (R Square) of 0.506 (50.6%). 2) There is a significant contribution of flexibility of the superiority of the hand to the ability of passing over with a coefficient of determination (R Square) of 0.447 (44.7%). 3). There is a significant contribution of arm muscle explosive power to the ability to pass over with a coefficient of determination (R Square) of 0.411 (41.1%) 4). There is a jointly significant contribution of eye-hand coordination, hand flexibility, and arm muscle explosive power to the upper passing ability with a termination coefficient (R Square) of 0.734 (73.4%)